Assessment of local community participation in peat swamp forest conservation and rehabilitation program in Selangor, Malaysia - Abdul Manaf, Mohd Basri (2016)
The general objective of the study is to evaluate the participation of local communities towards rehabilitation and conservation program for the peat swamp forest specifically the North Selangor Peat Swamp Forest (NSPSF) in strengthening sustainable forest management strategies and options in the state of Selangor. To address the research question to achieve the stated aim and objective of this study, mixed method research design was used. A consultation workshop was conducted to provide opportunity for interacting, especially between agencies and local communities on the Strength Weakness, Opportunity and Treat (SWOT) regarding the restoration and maintenance of NSPSF. Also, survey questionnaire was structured to obtain data on local participation in the rehabilitation and conservation of NSPSF and administer in selected localcommunities near the forest reserve. The results showed that the role of stakeholders in the restoration and conservation of NSPSF is very important. However, the findings showed that the level of involvement of local communities towards various stages of restoration and conservation activities NSPSF is low. Overall participation Index (IP) is 0.29 with the index level of monitoring is low (IP = 0.26). Also, the contributing factors to the level of participation of local communities in the recovery and conservation programs NSPSF were assessed. The results show that six of the eight independent variables and demographic characteristics of community involvement are significant. The 'predictor' level of community involvement in the restoration and conservation activities is strongly significant (β = 0.164, p < 0.01). Other parameter such as community involvement in committee Peat Swamp Forest Fire Disaster (β = 0.035), profit sharing (β = 0.032), community men (β = 0.024), own and operate the garden / farm near the peat swamp forest (β = 0.018), and age of the local community members (β = 0.0007) affect level of community participation in the restoration and conservation activities NSPSF at the 5% significance level. The implications of these findings should be focus more specifically at the design of programs to improve the level of local communities’ participation in the restoration and conservation activities NSPSF at all levels.